PERBEDAAN HASIL BELAJAR SISWA DENGAN MENGGUNAKAN MEDIA GAMBAR DAN MEDIA ALAT PERAGA PADA MATERI SISTEM PERNAPASAN MANUSIA DI KELAS XI IPA SMA PRAYATNA MEDAN - Nur Ainun (Jurnal Pelita Pendidikan, 2016)
Research to know what available distinctive result studies by use of image media and display toolmedias. Observational type that is utilized is experiment by give conduct to on the two observational samplegroup. Population in observational it is exhaustive student braze XI IPA SMA Prayatna Field which is as much 4classes by totals students 146 person. Observational sample to be taken two prescribed class arbitrarily, whichis. Experiment class (XI IA2) and Experiment class (XI IA3) each as much 38 students. Instrument that is utilizedin this research is essay deep shaped objektifitas which is for postest's problem as much 20 problems that theirwas declared for valid and reliabel. Before beforehand hypthosts testing to be tested normality andhomogeneity esays. Normality is tested by use of tech Liliefors and homogeneity by use of quiz F. Ofexamination that does to be gotten that sample second gets normal distribution and homogeneous. Acquiredobservational result that yielding average studies that chastened utilizes media image and display tool mediausufructs acquired hypthosts testing t computing >t table which is 7.98 > 0.78 on level = 0.05. Students learnedresult braze . Experiment to be gotten postest's average as big as 82.76. Meanwhile beajar's result studentbrazes Experiment II. postest's average as big as 76 . 44.Key word: Students Learnng result, Visual Media, display tool Media